Optimising Waqf Funds through the GoJariyah Digital Platform as a Halal Business Financing Instrument to Overcome the Trap of Online Loans - Rusny Istiqomah Sujono; Febrian Wahyu Wibowo; Anik Anik; Mufti Muyassarotul Farihah; Ragil Satria Wicaksana; Muhammad Kashif (FOUNDAE (Foundation of Advanced Education), 2026)
Small and medium enterprises (SMEs) often face barriers to business growth due to limited access to capital and the increasing reliance on high-interest online lending. This study aims to examine the implementation and impact of a waqf-based halal financing program designed to provide sustainable and interest-free capital for SMEs. The program represents a collaboration between YEWI and Alma Ata University through the GoJariyah platform, which promotes a fair and inclusive sharia-based financial ecosystem. The program was implemented from July 2024 to August 2025 in Yogyakarta using a community-based program design that included needs mapping, outreach, transparent beneficiary selection, and periodic evaluation supported by digital technology and partnerships with local Islamic financial institutions. Through this program, a total of IDR 300 million in productive waqf funds was distributed to 30 selected SMEs. The first year of implementation demonstrated positive outcomes. Beneficiary SMEs experienced an average revenue increase of 10–15%, with several businesses expanding production capacity and creating new employment opportunities. In addition to financial access, participating SMEs also showed improvements in business management practices, readiness for halal certification, and stronger integration into the local halal economic ecosystem. Overall, the findings indicate that waqf-based financing can serve as a practical and impactful model for supporting SME development. The GoJariyah program demonstrates the potential of productive waqf to strengthen small business resilience, reduce dependence on high-interest loans, and contribute to the development of the halal economy.